An Analytical Hierarchy Process-Based Evaluation of Food Estate Location Selection: A Case Study in Central Java - Poppy Arsil; Rifda Naufalin; Hana Hanifa; Ratna Satriani; Dhifan Kemal Akbar; Icuk Rangga Bawono; Rifky Dwi Prastomo (Journal of Applied Agricultural Science and Technology, 2026)
The food estate program is a governmental initiative designed to facilitate the integrated development of food systems within a designated area, including agriculture, plantations, and animal husbandry. The objective of the present study is first to identify the most suitable agricultural crop according to local determining characteristics; and second, to evaluate the land's suitability for each chosen agricultural crop. This study employed a combination of qualitative and quantitative methodologies. The qualitative study focused on the identification and analysis of the criteria used for the selection of suitable food estate locations and the determination of promising commodities within the study area. This was achieved through a series of focus group discussions (FGDs). Three FGDs were conducted with participants comprising provincial and regency-level government decision-makers and experts from local universities. Their insights contribute to the formulation and refinement of the selection indicators relevant to local conditions. The quantitative study employed the Analytical Hierarchy Process (AHP), enabling a systematic evaluation of expert priorities. To assess and rank the importance of key criteria influencing location selection decisions, eleven experts were interviewed. The AHP results have identified seven main criteria as being essential for determining the suitable locations for food estates in Purbalingga Regency. Pineapple has been identified as the most suitable, promising commodity for food estate development in Purbalingga Regency, as determined by the integrated assessment. This determination is based on the compatibility of pineapple with local environmental conditions, its market potential, and stakeholder preferences.